Finite element analysis and experimental study on contact pressure of hydraulic support bud-shaped composite sealing ring. (October 2016) - Zhang, Xi; Wang, Gang; Xia, Peng; Li, Hai-Peng; He, Ming
By the fluid dynamics theory analysis of the sealing interface, the importance of sealing contact pressure research for sealing performance is discussed. By experiments and data analysis for nitrile rubber buna and polyurethane, Mooney–Rivlin model parameters of two materials are obtained. By the finite element analysis of bud-shaped composite sealing ring under different pressures and secondary analysis, sealing contact pressure distribution curve of finite element analysis has been obtained. Sealing experimental apparatus is designed and assembled. The contact pressure distribution curve and three-dimensional pressure distribution field are obtained using the pressure-sensitive film. The results from finite element analysis and experiment are consistent with the conclusion of fluid dynamics theory analysis. The research content and design have great significance for sealing mechanism study.